2008
DOI: 10.1016/j.brainres.2008.08.066
|View full text |Cite
|
Sign up to set email alerts
|

A naloxonazine sensitive (μ1 receptor) mechanism in the parabrachial nucleus modulates eating

Abstract: The parabrachial nucleus (PBN) is an area of the brain stem that controls eating and contains endogenous opioids and their receptors. Previously, we demonstrated that acute activation of µ opioid receptors (MOPR) in the lateral PBN increased food consumption. MOPR's have been divided operationally into µ 1 and µ 2 receptor subtypes on the basis of the ability of naloxonazine (Nlxz) to block the former but not the latter. We used autoradiography to measure whether Nlxz blocks stimulation by the µ 1 /µ 2 agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The PBN is the most responsive brain region where benzodiazepine injection promotes taste reactivity (Berridge and Pecina, 1995). Direct injections of cannabinoid or mu-opioid receptor agonists into the PBN stimulate feeding (Chaijale et al, 2008;DiPatrizio and Simansky, 2008;Wilson et al, 2003). Thus, the PBN can process both aversive and appetitive ascending visceral information to modulate feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The PBN is the most responsive brain region where benzodiazepine injection promotes taste reactivity (Berridge and Pecina, 1995). Direct injections of cannabinoid or mu-opioid receptor agonists into the PBN stimulate feeding (Chaijale et al, 2008;DiPatrizio and Simansky, 2008;Wilson et al, 2003). Thus, the PBN can process both aversive and appetitive ascending visceral information to modulate feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, suppression was common to all three antagonists as was a rapid recovery to baseline. Relative to the other antagonists, the naloxone effect was delayed but similarly short-lived, which may relate to differences in the ability of each drug to penetrate neural tissue due to chemical structure or potency (see also Martin et al 2006 ; Chaijale et al 2008 ). It is noteworthy that the binding affinity of opioid antagonists to mu- and kappa-opioid receptors have been well-characterized for mammals, but not yet for teleost fishes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, work by Simansky and colleagues showed that opioid and endocannabinoid stimulation within parabrachial nucleus also robustly increases consumption of palatable food (Wilson et al, 2003; DiPatrizio and Simansky, 2008). Further, endogenous opioid function within PBN appears to be required for food motivation, as infusions of naloxonazine completely prevented DAMGO induced hyperphagia (Chaijale et al, 2008). …”
Section: 1 Parabrachial Nucleus Hotspotmentioning
confidence: 99%